ASYMPTOTICS OF SOLUTIONS OF DIFFUSION STOCHASTIC DIFFERENTIAL-FUNCTIONAL SYSTEMS WITH A SMALL PARAMETER UNDER THE ACTION OF EXTERNAL RANDOM VARIABLES - Ясинський, Володимир; Дорошенко, Ірина (SWorldJournal, 2022)
The paper considers averaging in stochastic differential equations without aftereffects under the action of external fixed random variables. Then this technique of proofs is transferred to averaging for stochastic differential-functional equations under